The Representation of LPDP Scholarship in CNN Indonesia: a Corpus Based Critical Discourse Analysis - Vita Diah Setyoningrum; Sulis Triyono; Ashadi Ashadi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Media tend to portray state-owned scholarships and can influence public opinion in a positive, negative, or neutral way. However, the specific depiction of the LPDP scholarship, a prominent state-owned scholarship in Indonesia, requires closer examination. The image of the LPDP scholarship can be analyzed through the collocation of keywords related to LPDP and LPDP scholarships found in the CNN Indonesia news data corpus. The role of the media in forming a positive or negative image is then critically examined through critical discourse analysis. Methodology: The method used in this study is critical discourse analysis using corpus tools. The data used are 77 news about LPDP Scholarships with a total of 26,335 tokens. The news text was analyzed with the help of a corpus tool in the form of the AntConc application to obtain word frequencies, collocations, and concordances. Findings: The image of the LPDP Scholarship in CNN Indonesia news is first seen from the frequency of words that appear and are significant, meaning that CNN Indonesia tends to be specific in reporting the LPDP Scholarship by directly referring to the program it has. Second, the emergence of collocation tends to focus on news about the LPDP Scholarship even though there was one negative image related to the problems that occurred in 2020. Third, the emergence of concordance gives the meaning that CNN Indonesia tends to provide a positive image of news about the LPDP Scholarship. Conclusion: The results of the study show that the frequency of words, collocations, and concordances that appear mean that the CNN Indonesia news media in reporting the LPDP Scholarship predominantly provides a positive image. The media tends to report specifically about the LPDP Scholarship, such as the registration and funding schemes. On the one hand, the media is neutral in reporting. This can be seen from how the media also portrays the conflict that occurred in the LPDP Scholarship, especially regarding the policies implemented. Originality: This study uses LPDP news in 2014-2024 released by CNN Indonesia to determine the image of LPDP scholarships based on word frequency, collocation, and concordance.